AN ANALYSIS OF CONVERSATIONAL IMPLICATURES OF THE MAIN CHARACTERS IN LADY BIRD FILM: A PRAGMATIC STUDY - Musdalifa Musdalifa; Surya Sili; Setya Ariani (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2022)
ABSTRACT Every participant involved in communication process is assumed to be cooperative so that the intentions of verbal activities can be achieved. However, in reality, sending purposes is not always conveyed straightforwardly. In practice, a person may not get to the point of the conversation where s/he is expected to speak honestly, informatively, relevant, and appropriately that are remarkably understood by the interlocutor. In terms of language, this phenomenon is known as the conversational implicature in which participants prefer to imply their extra or hidden meaning that is communicated behind utterances spoken. From that kind of phenomenon, this research aims to examine the  phenomenon in the conversation of the two main characters in the Lady Bird film by applying Grice's theory to determine the implicature form and Searle's illocutionary classification theory to determine the function of the implicatures as the main theories and the supporting theory by Hymes for portraying context of conversation which determines the factors that influence communication. This study also uses qualitative method and content analysis approach to process data in the form of dialogue to identify conversation implicatures which are categorized into two, namely generalized conversation implicature and particularized conversation implicature and the function classification in declarative, representative, directive, expressive and commissive form.Key words: cooperative principle, maxims, conversational implicature, illocutionary actsABSTRAK Dalam proses komunikasi, setiap partisipan diasumsikan bersedia untuk bekerja sama sehingga tujuan diadakannya kegiatan tersebut dapat tercapai. Penyampaian tujuan komunikasi pada kenyataannya tak selalu disampaikan secara lugas. Pada penerapannya, seseorang mungkin saja tidak langsung pada inti pembicaraan dimana si pembicara diharapkan untuk berbicara secara jujur, informatif, relevan, dan sesuai topik yang uniknya dapat dipahami dengan baik oleh lawan bicaranya. Dari sisi kebahasaan, fenomena tersebut dikenal dengan istilah implikatur percakapan dimana partisipan lebih memilih mengimplikasikan pesan mereka dengan mempertimbangkan konteks ujaran. Dengan kata lain, terdapat makna tambahan atau tersembunyi yang coba dikomunikasikan dibalik ujaran yang dituturkan. Berangkat dari fenomena itu, penelitian ini dimaksudkan untuk mengkaji fenomena komunikasi tersebut dalam percakapan dua tokoh utama di film Lady Bird dengan menerapkan teori utama dari Grice untuk mengetahui bentuk implikatur dan teori klasifikasi tindak ilokusi dari Searle untuk menentukan fungsi dari bentuk implikatur yang telah diidentifikasi serta teori pendukung dari Hymes untuk menggambarkan konteks ujaran yang menentukan faktor yang mempengaruhi komunikasi. Metode kualitatif dan pendekatan analisis konten diterapkan dalam kajian ini untuk mengolah data yang berupa dialog untuk mengidentifikasi implikatur percakapan yang dikategorikan menjadi dua yaitu implikatur percakapan umum dan implikatur percakapan khusus dan klasifikasi fungsinya yang berupa deklaratif, representatif, direktif, ekspresif dan komisif.Kata kunci: Implikatur percakapan, prinsip kerjasama, maksim, tindak ilokusi